Effect of carbon addition on the ferroelectric hysteresis properties of lead zirconate-titanate ceramic-cement composites - Chaipanich A. (2014)
Piezoelectric composites made from lead zirconate-titanate ceramic and cement have recently been developed as sensors in smart concrete structures due to their compatibility with the host concrete structure. However there is difficulty in poling the composite due to the insulating nature of the cement phase. In this work, carbon powder was used as a conducting phase in the composites at up to 2.0% by volume. The ferroelectric properties of the composites were investigated. For the same electric field, composites with added carbon were found to have higher polarization values. Therefore, this suggests that carbon could be added as a conducting phase to lead zirconate-titanate ceramic-cement composites in order to improve their polarization. © 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved. All rights reserved.